P-112 Increasing staff confidence and use of a handheld fan in the management of breathlessness. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Kerr, Margaret
Abstract : Background: Using a handheld fan has been identified in the literature as useful in the palliation of breathlessness (Luckett, Philips, Johnson et al ., 2017).There is continuing evidence that the handheld fan should be recommended to all breathless patients as an evidenced based management strategy for their symptoms (Galbraith, Fagan, Perkins et al ., 2010). It is also a useful intervention to recommend without qualification to any clinician or healthcare worker who sees breathless patients (Booth, Moffat & Burkin, 2011). Yet we know within the WHSCT within palliative care settings where breathlessness is a symptom, it is not being commonly considered or used. Aim: To increase staff confidence in identifying, providing and teaching use of the fan. To increase the use of the handheld fan in the palliative care inpatient settings within the WHSCT (palliative care in-patient unit and hospice in-patient unit). Methods: Training package developed including educational video and practical teaching session and delivered to nursing staff. Staff confidence measured pre- and post- training, at three months and at one year post training. Numbers of fans provided monitored. Results: Training is currently on-going in both locations and will be completed by 30/06/2018 when pre- and post- training confidence scores will be collated. To date, initial data shows 100% of high confidence scores post training. It will be most interesting to determine whether this confidence will be maintained at three months and one year. It is hoped that improved staff confidence scores will be achieved and maintained with resultant increased use of the handheld fan and improved management of the symptom of breathlessness. Conclusion: It is hoped that the anticipated results will demonstrate improved confidence and improved management of the symptom of breathlessness. Future plans will be centred on making the training available in other care settings and teams with resultant up-skilling of the workforce in non-pharmacological management of breathlessness in palliative care.